Reconciling activity-based descriptions of competence with professional work. Issue 4 (13th November 2017) - Lester, Stan
Abstract : Purpose: The purpose of this paper is to discuss the problems of applying competence standards to professional-level work, noting limitations in functional approaches and drawing on developments in professions and on a recent Erasmus+ project to propose a more adequate alternative. Design/methodology/approach: An approach to describing competence based on previously reported developments in some self-governing, principally British professions was used to inform an Erasmus+ project that created competence standards for five higher-level occupations in different European countries. Findings: The original developments in professions and further work through the project both endorse a model of competence that is based on standards of practice, applies holistically to professional or occupational fields rather than focusing on work roles and functions, respects contextual factors in defining competent action, and necessitates situational interpretation and judgement. Practical implications: Descriptions of professional competence need to avoid being overly constrained by assumptions about the roles that practitioners might perform or the context in which practice takes place. They need to reflect the ethos and ethics of the field as well as more transversal aspects of professionalism. Descriptions of this type are likely to reflect factors that are also valued in higher education. Originality/value: The model of competence that is proposed appears to have a good level of validity for high-level professional work, and provides an approach to describing practice that is not limited to particular national contexts.